2006
DOI: 10.1016/j.neuroimage.2006.02.016
|View full text |Cite
|
Sign up to set email alerts
|

EEG–fMRI of idiopathic and secondarily generalized epilepsies

Abstract: We used simultaneous EEG and functional MRI (EEG-fMRI) to study generalized spike wave activity (GSW) in idiopathic and secondary generalized epilepsy (SGE). Recent studies have demonstrated thalamic and cortical fMRI signal changes in association with GSW in idiopathic generalized epilepsy (IGE). We report on a large cohort of patients that included both IGE and SGE, and give a functional interpretation of our findings. Forty six patients with GSW were studied with EEG-fMRI; 30 with IGE and 16 with SGE. GSWre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
189
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(220 citation statements)
references
References 61 publications
26
189
3
2
Order By: Relevance
“…BOLD decreases have previously been reported in the DMN related to IEDs in temporal lobe epilepsy and generalised epilepsy (Archer et al, 2003;Hamandi et al, 2006) and are thought to reflect suspension of the resting state related to epileptic activity. Cases #1, 2 and 5 had mesial neo-cortical seizures with rapid EEG propagation, and BOLD decreases in the thalamus or basal ganglia.…”
Section: Bold Decreasesmentioning
confidence: 81%
“…BOLD decreases have previously been reported in the DMN related to IEDs in temporal lobe epilepsy and generalised epilepsy (Archer et al, 2003;Hamandi et al, 2006) and are thought to reflect suspension of the resting state related to epileptic activity. Cases #1, 2 and 5 had mesial neo-cortical seizures with rapid EEG propagation, and BOLD decreases in the thalamus or basal ganglia.…”
Section: Bold Decreasesmentioning
confidence: 81%
“…Such a secondary involvement of the DMN may also be causative for the clinical effects of other conditions affecting the temporal lobe/ limbic system such as schizophrenia 25 and Alzheimer's disease 22,26 . Prior studies have shown DMN involvement in TLE and other forms of epilepsy during seizures, during interictal epileptiform discharges, and in the interictal state 9,[28][29][30][31][32][33] . These studies indicate a potentially important role of the DMN in the interictal electrographic and the ictal behavioral characteristics of TLE.…”
Section: Discussionmentioning
confidence: 98%
“…In healthy subjects these regions are negatively activated using a task-rest paradigm and are functionally connected at rest and during some passive sensory processing (Greicius et al, 2003). Similarly, these regions have demonstrated primarily negative fMRI activation resulting from epileptic spiking in studies with simultaneous EEG/fMRI in generalized epilepsy (Archer et al, 2003;Salek-Haddadi et al, 2003;Aghakhani et al, 2004;Hamandi et al, 2006;Laufs et al, 2006). Kobayashi et al (Kobayashi et al, 2006b) and Salek-Haddadi et al (Salek-Haddadi et al, 2006) also found negative activation due to EEG spiking in default-mode regions in approximately 12% and 11.1% of focal epilepsy patients, respectively.…”
Section: Default-mode Network Activationmentioning
confidence: 98%
“…In this group of patients with temporal lobe epilepsy, we focused on temporal lobe activations and concordance with the epileptogenic region. Additionally, default-mode region activation is also reported, considering recent interest in this network (Archer et al, 2003;Salek-Haddadi et al, 2003;Aghakhani et al, 2004;Gotman et al, 2005;Hamandi et al, 2006;Kobayashi et al, 2006b;Laufs et al, 2006;Salek-Haddadi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%